Efeito da sexagem e de linhagens no desempenho e rendimento de carcaça de frangos de corte - Api, Ivandro (2014)
The objective was to evaluate the performance and carcass yield of different strains and sexing of broilers. The study was conducted at UTFPR with 576 birds of Cobb, Ross and Hubbard, arranged as male, female or mixed sexing, arranged in a completely randomized design (DIC) in a 3 x 3 factorial (strains x sexing), with four replications in each treatment and 16 birds in each experimental unit. Conducted daily monitoring, with weighing and calculation of feed intake and feed conversion weekly. At slaughter, carcass yield and cuts of each treatment was performed. Data were used from 141 slaughtered batches from February a December, 2012, relating to integrated poultry cooperative in the Southwest Region of Paraná, with the performance data of the same lines and sexagens producers in other comparative. For data analysis using the statistical program Assistat. Body weight, weight gain, feed intake and feed conversion were significantly on over the course of the evaluated phases differences, but in the end there were no significant differences. The performance of male presented superior in all parameters. Carcass yield was not observed significant differences between strains and sexagens birds but for some highlights cuts to Cobb. On data from the batches Hubbard provided higher mortality, body weight, daily weight gain, feed efficiency, productive efficiency and density. There was interaction between strain and sexing, presenting the best male Hubbard animal performance. There are differences between animal husbandry and sexing strains used in poultry production.